2018
DOI: 10.2134/jeq2018.02.0082
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dosing Increases Nitrate Removal Rates in Denitrifying Bioreactors at Low‐Temperature High‐Flow Conditions

Abstract: Nitrogen losses from croplands contribute to impairment of water bodies. This laboratory experiment evaluated various C sources for use in a denitrifying bioreactor, a conservation practice designed to reduce N losses. The nitrate removal efficiency of candidate treatments (corn cobs [CC], corn cobs with modified coconut coir [CC+MC], corn cobs with modified coconut coir and modified macadamia shell biochar [CC+MC+MBC], wood chips [WC], wood chips with hardwood biochar [WC+BC], and wood chips with continuous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
2
32
1
Order By: Relevance
“…Slopes of the linear regression across treatment groups in both DRW 2018 and DRW 2017 studies were 7.0 to 8.6. These results show that increased DRW duration led to greater DOC export, supporting the hypothesis that these aerobic periods release more labile DOC and help overcome the C limitation of denitrification believed to occur in woodchip bioreactors with recalcitrant, lignin-heavy media (Saliling et al, 2007;Cameron and Schipper, 2010;Feyereisen et al, 2016;Roser et al, 2018). Degradation of lignin by anaerobic respiration is negligible (Zeikus et al, 1982;Holt and Jones, 1983;Odier and Monties, 1983), with lignin breakdown primarily accomplished through aerobic microbes or fungi (Kirk and Farrell, 1987).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Slopes of the linear regression across treatment groups in both DRW 2018 and DRW 2017 studies were 7.0 to 8.6. These results show that increased DRW duration led to greater DOC export, supporting the hypothesis that these aerobic periods release more labile DOC and help overcome the C limitation of denitrification believed to occur in woodchip bioreactors with recalcitrant, lignin-heavy media (Saliling et al, 2007;Cameron and Schipper, 2010;Feyereisen et al, 2016;Roser et al, 2018). Degradation of lignin by anaerobic respiration is negligible (Zeikus et al, 1982;Holt and Jones, 1983;Odier and Monties, 1983), with lignin breakdown primarily accomplished through aerobic microbes or fungi (Kirk and Farrell, 1987).…”
Section: Resultssupporting
confidence: 65%
“…To the authors' knowledge, a method yielding such a dramatic increase in NO 3 removal rates in woodchip bioreactors without requiring additional energy or chemical inputs (e.g., C dosing, heating, electrical stimulation, etc.) has not been reported (Cameron and Schipper, 2011;Law et al, 2018;Roser et al, 2018). Further research is required to quantify total C loss from woodchips since DRW cycles will decrease woodchip lifespan.…”
Section: Discussionmentioning
confidence: 98%
“…This could stimulate N removal in winter, when C availability from wood chips might be lower due to low temperature. An example of this using acetate instead of ethanol as additional substrate was described recently (Roser et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Woodchip bioreactors are the most tested technology, where simple structures intercept drainage waters and facilitate nutrient removal through addition of a carbon source to stimulate biological denitrification that converts nitrate to nitrogen gas. Physico-chemical treatments placed after bioreactors have also been proposed to improve nutrient removal using a wide variety of materials (Jaynes et al 2008;Buda et al 2012;Hussain et al 2014;Hua et al 2016;Roser et al 2018). For example, Salo et al (2015) demonstrated that a woodchip bioreactor system with iron media as post-treatment removed nitrate and phosphate from subsurface drainage.…”
Section: Mitigation Of Subsurface Drain Nutrient Losses Through Contrmentioning
confidence: 99%